Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/adsc.201301148
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Capsaicin Analogues from Lignin‐Derived Compounds by Combined Heterogeneous Metal, Organocatalytic and Enzymatic Cascades in One Pot

Abstract: The total synthesis of capsaicin analogues was performed in one pot, starting from compounds that can be derived from lignin. Heterogeneous palladium nanoparticles were used to oxidise alcohols to aldehydes, which were further converted to amines by an enzyme cascade system, including an amine transaminase. It was shown that the palladium catalyst and the enzyme cascade system could be successfully combined in the same pot for conversion of alcohols to amines without any purification of intermediates. The inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 41 publications
(43 reference statements)
0
28
0
1
Order By: Relevance
“…Neither the ( S )‐selective ATA from Chromabacterium violaceum (ATA‐Cvi) and its mutant W60C,18 nor six ( R )‐selective ATAs led to a conversion when combined with a large alanine excess (80–200 equiv., see Supporting Information, Table S1 for tested enzymes). Also, when combined with an enzyme cascade ( L ‐alanine dehydrogenase and glucose dehydrogenase19) to shift the equilibrium, ATA‐Cvi did not yield the desired amino alcohol. However, benzylamine was formed as a side‐product with conversions up to 52% (HPLC Method 1, see Supporting Information for all analytics).…”
Section: Resultsmentioning
confidence: 99%
“…Neither the ( S )‐selective ATA from Chromabacterium violaceum (ATA‐Cvi) and its mutant W60C,18 nor six ( R )‐selective ATAs led to a conversion when combined with a large alanine excess (80–200 equiv., see Supporting Information, Table S1 for tested enzymes). Also, when combined with an enzyme cascade ( L ‐alanine dehydrogenase and glucose dehydrogenase19) to shift the equilibrium, ATA‐Cvi did not yield the desired amino alcohol. However, benzylamine was formed as a side‐product with conversions up to 52% (HPLC Method 1, see Supporting Information for all analytics).…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] The inclusion of heterogeneous catalysis is highly desirable since it would allow for different reactivity not possible using homogeneous organometallic catalysts (e.g reductions and oxidations) and allow for facile removal and recycling of the transition metals. 8 It can also be implemented in flow-chemistry processes.…”
mentioning
confidence: 99%
“…In an excellent example of the flexible use of multiple biocatalysts, Berglund et al reported a total synthesis of capsaicin analogues from a primary alcohol 47 using a metal‐catalyzed oxidation to produce aldehyde 48 , followed by a one‐pot amine transaminase‐catalyzed reductive amination and a lipase‐catalyzed amidation, using a fatty acid as the acyl donor (Scheme ) . The authors initially investigated the use of a biocatalyzed oxidation, which could be coupled with the amine transaminase; the alcohol dehydrogenase could function as a redox partner for the regeneration of cofactors for the l ‐alanine dehydrogenase ( l ‐AlaDH) as well as the oxidation of the alcohol 47 .…”
Section: Examples Of Enzymes In Pharmaceutical and Natural Product Smentioning
confidence: 99%